Pengaruh Efektivitas Penyaluran Bantuan Pangan Non Tunai (BPNT) Terhadap Upaya Penanggulangan Masyarakat Prasejahtera di Desa Salem - Rinda Mayang Sari; Arief Mulyawan Thoriq; Adriansyah Adriansyah (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
This research was conducted in areas that have been designated as beneficiaries of the Non-Cash Food Assistance program, namely in Salem Village, Pondoksalam District, Purwakarta Regency. The aims of this study were 1) To determine the effectiveness of the distribution of Non-Cash Food Assistance (BPNT) in Salem Village, Pondoksalam District, Purwakarta Regency, 2) To determine efforts to overcome the underprivileged community in Salem Village, 3) To determine the effect of the effectiveness of the distribution of Non-Cash Food Assistance on efforts to overcome underprivileged communities in Salem Village. This study uses quantitative methods with Simple Linear Regression analysis. The data collection technique used a questionnaire or questionnaire method and obtained 63 respondents from BPNT recipients. It was analyzed using a statistical tool, namely SPSS version 25. Based on the results of data processing from the distribution of the questionnaire, there was a significant effect on the effectiveness of the distribution of non-cash food assistance on efforts to overcome the underprivileged community in Salem Village, Pondoksalam District, Purwakarta Regency. This can be seen from the results of the R Squer of 0.0841 or 84.1% and from the results of the regression analysis obtained a significance value of 0.000 <0.05 so it can be concluded that there is a significant influence between the effectiveness of the distribution of Non-Cash Food Assistance (BPNT) on efforts to overcome underprivileged communities in Salem Village.